Communication of Deep South’s Young People in the Physical Community and Online Platforms amidst the COVID-19 Pandemic - Sattar, Yasmin; นิลปัทม์ สมัชชา; Sahoh, Imron (Journal of Social Sciences and Humanities Research in Asia, 2022)
This research aims to study how the youth in southern most provinces of Thailand adapt their communication, and and to improve their forms of proactive communication mechanism in the community and online community during the COVID-19 pandemic. This qualitative research used document analysis and nine in-depth interviews from the Motive, MUSLIMITED, and young people in Bannang Sata, representing Pattani, Yala, and Narathiwat, and workshops with the target groups as well as local media organizations. Data analysis was done with the concept of crisis communication. The study reveals that young people played a supportive role in communicating in crisis of such pandemic, especially through online platforms. With regard to community communication, the youth tend to be able to access various data, to verify fake news, and to communicate by using creative methods both physically and virtually. Though the roles of youth in the deep south during the COVID-19 epidemic could visibly been seen, no systematic mechanism has not yet been established. As a result, the community and local media in the deep south should have clear measures to deal with any possible crisis as well as mechanisms for having everyone, especially the youth, take part. That will help the state’s mechanisms when the latter fail to function efficiently, and to support them as they gradually improve, as that needs to be designed based on the local necessities.